Emergency Care for Suicidal Behavior Before and During the COVID-19 Pandemic in Two Hospitals in Bogotá: a Longitudinal Analysis - Gutiérrez-Dajud, Sasha Stefany; Pastran-Cortés, Ana María; Mendivelso, Fredy; Rodríguez-Bedoya, Ingrid Milena; Moreno-Gómez, Jairo Enrique; Muñoz-Tamayo, Rodrigo (Iatreia)
Introduction: The impact of the COVID-19 pandemic and confinement measures on the pattern of admissions for suicidal behavior in emergency departments is unknown. Methods: A retrospective longitudinal cohort study was conducted, collecting monthly data from January 2015 to June 2022 from the mental health program of two reference institutions in Bogota. All patients were assessed by psychiatrists and psychologists in the emergency department and their demographic, clinical and specific attributes of suicidal behavior were characterized. An interrupted time series analysis was performed to evaluate the trend and impact on the pattern of care before and during the pandemic. Results: A total of 884 individuals were admitted for suicidal behavior during the study period (67% women, 66% young adults, 55% students, and 1.6% LGBTQ+ population). There was an increase in the number of cases attended (mean of 5 additional cases per month) compared to the prepandemic period (p < 0.000). Suicidal ideation was the most documented typology during the pandemic (p <0.001), and the prevalence of suicidal behavior among children and adolescents (≤18 years) increased from 29% to 33%. Conclusions: Theresults suggest that the pandemic catalyzed the number of admissions for suicidal behavior in the general population after the implementation of containment measures or contagion prevention restrictions. The need to integrate emergency departments in the prevention, detection, management, and follow-up of suicidal behavior, especially in the current mental health epidemic, is underscored.